1994
DOI: 10.1007/bf00046093
|View full text |Cite
|
Sign up to set email alerts
|

The effects of silver nitrate, colchicine, cupric sulfate and genotype on the production of embryoids from anthers of tetraploid wheat (Triticum turgidum)

Abstract: Anther culture of four tetraploid wheat (Triticum turgidum) genotypes was studied using ten different culture medium treatments in a randomized block design with four replicates. Each replicate consisted of 2 pots with 3 plants. Anther donor plants were grown in a greenhouse with a 16 h day / 8 h night at 25°C and 15°C, respectively. The first treatment which was considered as the control, was potato 2 medium modified by adding 0.5 g 1-1 glutamine and solidified by gelrite (4 g 1-1). The nine test treatments d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
18
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 16 publications
6
18
0
Order By: Relevance
“…Similar results were also found for wheat anther cultures and triticale immature embryo-derived callus (Purnhauser and Gyulai, 1993). Ghaemi et al (1994) tested the effects of different copper levels on the production of embryoids from anthers of tetraploid wheat (T. turgidunt L.), and found that the addition of 40 µM CuSO 4 to the medium significantly increased embryoid production in three of the four genotypes tested. Chen et al (2004) showed a positive correlation between the rate of wheat callus regeneration and concentration of Cu 2+ in the culture medium, and suggested that the optimal concentration of Cu 2+ for wheat tissue culture is 5 µM.…”
Section: Discussionsupporting
confidence: 69%
“…Similar results were also found for wheat anther cultures and triticale immature embryo-derived callus (Purnhauser and Gyulai, 1993). Ghaemi et al (1994) tested the effects of different copper levels on the production of embryoids from anthers of tetraploid wheat (T. turgidunt L.), and found that the addition of 40 µM CuSO 4 to the medium significantly increased embryoid production in three of the four genotypes tested. Chen et al (2004) showed a positive correlation between the rate of wheat callus regeneration and concentration of Cu 2+ in the culture medium, and suggested that the optimal concentration of Cu 2+ for wheat tissue culture is 5 µM.…”
Section: Discussionsupporting
confidence: 69%
“…In this species green plants have been regenerated at a low frequency because most of the genotypes did not respond at all to anther culture, or because most plantlets regenerated were albino (Hadwidger and Heberle-Bors 1986;Foroughi-Wehr and Zeller 1990;Cattaneo et al1991;Orlov et al 1993;Otani and Shimada 1994;Ghaemi et al 1995;J'Aiti et al 1999J'Aiti et al , 2000Silva-Romano and Canhoto 1999;Dogramaci-Altuntepe et al 2001;Jauhar 2003b). Furthermore, significant genotype by stress pre-treatments (Mentenwab and Sarrafi 1997), genotype by medium composition (Ghaemi et al 1994) and genotype by cytoplasm interactions (Ghaemi et al 1993) have been described. Additionally, when green plants were obtained (Dogramaci-Altuntepe et al 2001) high numbers of aneuploids were regenerated from the androgenic calli.…”
Section: Introductionmentioning
confidence: 99%
“…These authors used 5 mg·L −1 of silver nitrate in culture media, and manage to reduce the growth rate of plants, increasing the period of subculture in more than six months. Before, in an investigation with wheat, verified that the addition of the same 5 mg·L −1 silver nitrate significantly increased the percentage of anther response rate in the formation of somatic embryos [36].…”
Section: Resultsmentioning
confidence: 91%